Association of 3-dimensional facial changes and height and weight increase in children: A 2-year follow-up - Kamínková, Petra; Dírer, Peter; Fudalej, Piotr (American journal of orthodontics and dentofacial orthopedics, 2022)
INTRODUCTION: This study aimed to evaluate changes in facial size and shape in children and their relationship to the changes in height and weight. METHODS: One hundred and thirteen healthy children aged between 6 and 13 years were followed annually for 2 consecutive years. The facial morphology was captured in 12-month intervals (from T1 to T2 and from T2 to T3) using a 3-dimensional stereophotogrammetric optical scanner; the body height and weight were recorded simultaneously. The changes in facial size and shape were analyzed with geometric morphometrics. Multiple regression mixed-effects models were exploited for evaluation of the association between the changes of facial size or shape and age at the beginning of the observation, gender, and change of height and weight. RESULTS: The centroid size (reflecting facial size) increased from T1 to T2 and T2 to T3 in boys and girls. In contrast, the facial shape did not change during both 12-month observation periods (T1 to T2 and T2 to T3) either in boys or girls. Of 2 multiple regression mixed-effects models, only the model with the change of natural logarithm of centroid size as a dependent variable was statistically significant (P <0.001; adjusted r2 = 0.29). It showed that height and weight changes were associated with a change of the facial size (with weight change having a greater effect than height change: adjusted r2 = 0.25 for weight change and adjusted r2 = 0.106 for height change). CONCLUSIONS: Most changes in the facial morphology observed in our cohort were associated with increasing facial size. In contrast, the shape of the face remained relatively constant. Body height and weight gains were associated with the change of the facial size only. However, only 29% of the variation in facial size was explained by height or weight changes during growth.
Keywords: Body Height; Face; Female; hmotnostní přírůstek; dítě; ženské pohlaví; Weight Gain; Adolescent; lidé; následné studie; tělesná výška; obličej; Photogrammetry; Follow-Up Studies; Male; fotogrammetrie; Child; mužské pohlaví; mladiství; Humans